Forgetful polygons as generalizations of semi-affine planes - Govaert, E.; Van Maldeghem, H. (Discrete mathematics, 2003)
We generalize the notion of a semi-affine plane to structures with higher girth n. We prove that, in the finite case, for n odd, and with an additional assumption also for n even, these geometries, which we call forgetful n-gons, always arise from (finite) generalized n-gons by ‘forgetting’ lines.